The Framework for Estimating the Discount Rate of Insurance Contracts based on the International Financial Reporting Standard No. 17 - Ali Rahmani; Leili Niakan; Mahnaz Mahmoudkhani; Alin Avasapian (پژوهش‌های تجربی حسابداری)
In May 2017, the International Accounting Standards Board (IASB) published International Financial Reporting Standard No. 17 (IFRS 17), titled Insurance Contracts. IFRS 17 establishes principles for the recognition, measurement, presentation, and disclosure of insurance contracts, reinsurance contracts, and investment contracts with discretionary participation features. The adoption of IFRS 17 can significantly impact financial management frameworks, profit, equity, reserves, financial reporting processes, and actuarial models. IFRS 17 introduces a novel approach to determining the discount rate for insurance liabilities, which is a critical component in calculating the present value of future cash flows associated with insurance contracts. The primary objective of this study is to develop a framework for estimating the discount rate of insurance contracts in accordance with IFRS 17 in Iran. This research is applied in nature and employs a descriptive, survey-based method for data collection. A questionnaire served as the data collection tool. The statistical population comprises financial managers, actuaries, internal auditors, and risk managers, with a total of 85 valid questionnaires received. Group mean comparison tests and analysis of variance (ANOVA) were used to evaluate the opinions of different respondent groups regarding the research objective. The results of the mean comparison indicate that with the exception of propositions related to selecting the rate of government debt bonds as the market rate and choosing a reference portfolio based on theoretical assets, other propositions such as incorporating liquidity features into insurance contracts, the availability of observable affordable price data in financial instruments, the use of market-based inputs to determine the discount rate, the application of top-down and bottom-up approaches in setting the discount rate, the annual determination of the discount rate for insurance contracts, the sensitivity of insurance liability assessment results, and the determination of the discount rate by the board of directors were found to be significant. Additionally, the results of the variance analysis and Tukey’s test revealed significant differences among the opinions of respondent groups concerning the liquidation claims of health insurance, property insurance, and liability insurance; the use of a customized portfolio as a reference portfolio; the alignment between the maturity of real assets in the reference portfolio and the liabilities of insurance contracts; and the use of the technical interest rate or accrual rate to calculate insurance premiums in life insurance.